2018
DOI: 10.3389/fpls.2018.01020
|View full text |Cite
|
Sign up to set email alerts
|

Increased Cytosolic Calcium Contributes to Hydrogen-Rich Water-Promoted Anthocyanin Biosynthesis Under UV-A Irradiation in Radish Sprouts Hypocotyls

Abstract: Our previous studies showed that hydrogen-rich water (HRW) promoted the biosynthesis of anthocyanin under UV-A in radish. However, molecular mechanism involved in the regulation of the anthocyanin biosynthesis is still unclear. In this study, the role of calcium (Ca2+) in HRW-promoted anthocyanin biosynthesis in radish sprouts hypocotyls under UV-A was investigated. The results showed that a positive effect of HRW on the content of cytosolic calcium and anthocyanin accumulation, mimicking the effects of induce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 73 publications
3
10
0
Order By: Relevance
“…And the up-regulated ZmSOS1 and ZmSKOR in the combined HRW and NaCl treatment might suggested positive role of above 2 genes under saline conditions, which also agreed with the higher K + /Na + ratio in the combined treatment. The SOS pathway is activated by cytosolic Ca 2+ , Zhang demonstrated that HRW treatment could increase the cytosolic Ca 2+ [29]. Here, CDPK21 was of especially interest to us, because it was much more responsive to HRW.…”
Section: Discussionmentioning
confidence: 91%
“…And the up-regulated ZmSOS1 and ZmSKOR in the combined HRW and NaCl treatment might suggested positive role of above 2 genes under saline conditions, which also agreed with the higher K + /Na + ratio in the combined treatment. The SOS pathway is activated by cytosolic Ca 2+ , Zhang demonstrated that HRW treatment could increase the cytosolic Ca 2+ [29]. Here, CDPK21 was of especially interest to us, because it was much more responsive to HRW.…”
Section: Discussionmentioning
confidence: 91%
“…IP3 can induce isoflavone accumulation in soybean sprouts by upregulating the activity of isoflavone biosynthetic enzyme under UV-B radiation (Jiao et al, 2016). Similarly, there is a high correlation between IP3 content and anthocyanin accumulation in radish sprouts (Zhang et al, 2018a). In this study, exogenous calcium increased the IP3 content in hypocotyls, and there was a significant correlation with the anthocyanin content (Figure 4).…”
Section: Discussionsupporting
confidence: 61%
“…The total anthocyanin content was extracted from the corresponding hypocotyl tissue using an extraction solution (49.9% ddH 2 O, v/v; 50% methanol, v/v; and 0.1% HCl v/v), and measured as described in the previous study (Zhang et al, 2018a).…”
Section: Anthocyanin Extraction and Measurementmentioning
confidence: 99%
“…The calcium accumulation in root cells was measured by the Fluo-3/AM (calcium fluorescent probes; catalog no. 39294, Sigma-Aldrich) based on the method of Yan et al (2015) and Zhang et al (2018). Briefly, the root samples were immersed in incubation solution (containing 20 mM Fluo-3/AM, 0.5 M mannitol, 4 mM MES [pH 5.7] and 20 mM KCl) for 30 min at a room temperature.…”
Section: Histochemical Detection Of H 2 O 2 and Ca 21mentioning
confidence: 99%
“…Jin et al (2016) found that under drought stress, H 2 rapidly increased H 2 O 2 and modified the apoplastic pH of leaves in alfalfa via an abscisic acid-based mechanism. Furthermore, incremental IP3dependent cytosolic Ca 21 contributes to H 2 -promoted anthocyanin biosynthesis under UV-A irradiation in radish sprouts (Zhang et al, 2018).…”
mentioning
confidence: 93%